2011
DOI: 10.1007/s10120-011-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

Second-line chemotherapy for gastric cancer: a new issue lies ahead in global trials

Abstract: Chemotherapy for gastric cancer has been advancing fairly well. It has been indicated that not only advances in first-line chemotherapy but also those in second-line chemotherapy have contributed to the prolongation of overall survival. The Arbeitsgemeinschaft Internistische Onkologie (AIO) study supports the idea that second-line chemotherapy is appropriate in patients with a good general condition. Also, the Japan Clinical Oncology Group (JCOG) integral analysis suggests that advances have been made in secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In particular, paclitaxel, docetaxel, and irinotecan have been identified promising drugs whether in combination regimens or as single agents. According to the results of several recent studies, the patient response rates ranged from approximately 10% to 20%, and the PFS ranged from 2.5 to 4.0 months [14]. Interestingly, the survival period following the failure of first-line chemotherapy has been shown to be longer in Asia than in Western countries, possibly due to the higher proportion of patients who receive subsequent chemotherapy in Asia and differences in the patient characteristics [15].…”
Section: Overview Of First- and Second-line Chemotherapy For Agcmentioning
confidence: 99%
“…In particular, paclitaxel, docetaxel, and irinotecan have been identified promising drugs whether in combination regimens or as single agents. According to the results of several recent studies, the patient response rates ranged from approximately 10% to 20%, and the PFS ranged from 2.5 to 4.0 months [14]. Interestingly, the survival period following the failure of first-line chemotherapy has been shown to be longer in Asia than in Western countries, possibly due to the higher proportion of patients who receive subsequent chemotherapy in Asia and differences in the patient characteristics [15].…”
Section: Overview Of First- and Second-line Chemotherapy For Agcmentioning
confidence: 99%
“…Chemotherapy with less toxicity, better disease control and life prolongation should be considered preferentially. Some phase II trials showed that combination chemotherapy achieved no marked survival benefits in the second-line setting ( Takiuchi, 2011 ; Kang et al , 2012 ). Therefore, we chose not combination but single agent for the second-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple drugs have been evaluated as second-line therapy in phase II trials and retrospective cohorts, there have been no randomized head-to-head trials designed to establish a standard treatment in this setting [43]. Comparisons of second-line therapy across clinical studies are problematic for multiple reasons, including the nature of previous chemotherapy and responses to first-line chemotherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in advanced gastric cancer since response duration to first-line chemotherapy is prognostic for the benefit of second-line chemotherapy [44, 45]. With targeted agents being increasingly tested in conjunction with first-line chemotherapy, it will be important to evaluate how they impact the activity of subsequent second-line treatment and, conversely, how second-line therapy affects outcomes measured with first-line regimens [43]. …”
Section: Discussionmentioning
confidence: 99%